2006
DOI: 10.1007/s11172-006-0484-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation and properties of the nanocluster structure of iron oxides

Abstract: Nanostructures based on iron oxide clusters 1-300 nm in size were synthesized and studied. Thermodynamic models of nanocluster nucleation resulting in the formation of both primary nanoclusters and nanocluster aggregates with the sizes up to 70-80 nm were consid ered. Models of heat capacity of the nanoclusters were examined, and the twofold increase in the heat capacity of the iron oxide clusters 2-3 nm in size compared to that of the bulk iron oxide samples was found. The size of the primary nanoclusters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Nanoparticle oxides have applications in areas such as magnetism, catalysis, and medicine. 4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Iron oxide is particularly interesting because it consists of four major bulk phases, all of which exhibit unique properties. [1][2][3] FeO, wüstite, has a rock salttype structure with defects, generally referred to as Fe 1-x O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle oxides have applications in areas such as magnetism, catalysis, and medicine. 4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Iron oxide is particularly interesting because it consists of four major bulk phases, all of which exhibit unique properties. [1][2][3] FeO, wüstite, has a rock salttype structure with defects, generally referred to as Fe 1-x O.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These individual phases have been the subjects of many experiments involving films 12 and nanoparticles. 13,14,17,19,21 Gas phase experiments have also been performed to investigate properties such as bonding, reactivity, and structure of small cluster oxides. 23-56 Theory has provided a further understanding of the structures and stabilities of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…The fluctuation rate dramatically decreases with increasing particle size, and the mag netic moment becomes fixed relative to a particle. By comparing the results of this study with the data reported in [26,27], one may assume that the varia tions in the catalyst activity are associated with changes in both sizes and, probably, magnetic proper ties of the particles.…”
Section: Resultsmentioning
confidence: 57%
“…The Mössbauer spectra and magnetic properties were studied in [26,27] for Fe 2 O 3 particles obtained using the same method as in [25], i.e., the thermal decomposition of iron oxalate at different tempera tures, which was accompanied by changes in both the sizes and magnetic properties of the particles. Based on the performed measurements, the authors of [27] concluded that the first order magnetic phase transi tion occurs upon increasing particle size; i.e., super paramagnetic particles are transformed into magneti cally ordered ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation